Prevalence of Malassezia spp. in the external ear canals of dogs from Gorgan, Iran and analysis of some predisposing factors - A. Mikaeel; S. M. H. Karouei; H. R. Pordeli (Bulgarian Journal of Veterinary Medicine)
Yeasts of the genus Malassezia grow in areas with sebaceous glands like ears due to their reliance on lipids. This study aimed to identify the prevalence and population size of different species of Malassezia in the external ear canal of dogs. Additionally, possible correlations between the occur-rence of Malassezia yeasts and the sex, age, breed, and skin/ear disease history of the dogs were as-sessed. One hundred ear swabs from both ears of 50 dogs were collected. The collected samples were directly observed by the KOH wet mount method under the ‎microscope. Then, they were subjected to fungal culture and incubated. Staining was ‎done by the Gram method. The prepared spreads were observed ‎and examined with an ×100 microscope lens. For identifying yeast colonies, three bio-chemical tests containing catalase, ‎different percentages of Tween, and aesculin hydrolysis were used. PCR molecular test was used to confirm the ‎diagnosis of the identified yeast species and its data was matched with the identified cases.‎ The prevalence of M. pachydermatis and M. furfur was 44% and 6% respectively. Infection by Malassezia species was most prevalent in the native breed (78.26%). There was a higher incidence of Malassezia yeast contamination in female dogs (60.71%). The fre-quency of fungal species in dogs more than 2 years old was higher. There was a significant difference between the prevalence of Malassezia species frequency and the breed of the dogs (P=0.003) but no significant differences were found correlated with sex, age, and skin/ear disease history of the dogs.